Vem är det som styr egentligen? : en studie om styrning i den enskilda järnvägsfrågan 1862–1875 - Weibull Moberger,Pontus (2025)
Who is Truly in Charge? A Study of Local Governance Regarding the Private Railway Question, 1862–1875. This paper examines the concept of governance by situating it within the historical context of Swedish municipal self-government between 1862 and 1875. Focusing on selected municipal appeal cases concerning decisions on the construction of private railways, the study tests the applicability of governance as both a theoretical and analytical framework in a historical setting. By doing so, it seeks to assess whether governance provides a productive interdisciplinary perspective for understanding local decision-making processes and the dynamics of self-government and sovereignty during the early phase of Sweden’s democracy. The analysis further explores whether this approach can offer a more nuanced interpretation of prevailing notions of state sovereignty in Sweden, in the nineteenth century.
Keywords: Governance; staten; 1800-talet; enskilda järnvägar; besvär; Kungliga Majestäts befallningshavande